GSK3 activity regulates rhythms in hippocampal clock gene expression and synaptic plasticity. Issue 8 (27th May 2017) - Besing, Rachel C.; Rogers, Courtney O.; Paul, Jodi R.; Hablitz, Lauren M.; Johnson, Russell L.; McMahon, Lori L.; Gamble, Karen L.
Abstract: Hippocampal rhythms in clock gene expression, enzymatic activity, and long‐term potentiation (LTP) are thought to underlie day–night differences in memory acquisition and recall. Glycogen synthase kinase 3‐beta (GSK3β) is a known regulator of hippocampal function, and inhibitory phosphorylation of GSK3β exhibits region‐specific differences over the light‐dark cycle. Here, we sought to determine whether phosphorylation of both GSK3α and GSK3β isoforms has an endogenous circadian rhythm in specific areas of the hippocampus and whether chronic inhibition or activation alters the molecular clock and hippocampal plasticity (LTP). Results indicated a significant endogenous circadian rhythm in phosphorylation of GSK3β, but not GSK3α, in hippocampal CA1 extracts from mice housed in constant darkness for at least 2 weeks. To examine the importance of this rhythm, genetic and pharmacological strategies were used to disrupt the GSK3 activity rhythm by chronically activating or inhibiting GSK3. Chronic activation of both GSK3 isoforms in transgenic mice (GSK3‐KI mice) diminished rhythmic BMAL1 expression. On the other hand, chronic treatment with a GSK3 inhibitor significantly shortened the molecular clock period of organotypic hippocampal PER2::LUC cultures. While WT mice exhibited higher LTP magnitude at night compared to day, the day–night difference in LTP magnitude remained with greater magnitude at both times of day in mice with chronic GSK3 activity. On the other hand, pharmacological GSK3 inhibition impaired day–night differences in LTP by blocking LTP selectively at night. Taken together, these results support the model that circadian rhythmicity of hippocampal GSK3β activation state regulates day/night differences in molecular clock periodicity and a major form of synaptic plasticity (LTP).